الشفـــــــــــافيــــــــة واثــــــرها على جودة الـــرســـالــــــة الاعـــــــلانـــيــــــة لشــــركــــات التامين: بحث تطبيقي فـي شركة التامين الوطنية (Journal of Accounting and Financial Studies ( JAFS ), 2020)
Transparency is considered as one of the modern administrational terms which started to be largely used in the last period, because of its political, economical, social and cultural dimensions. As well as, its administrational dimension that helps to create a work environment marked by order and flawless from wrong practices and Transparency provides credibility to the sides that pursue it in their practices, till it became a mean of distinction. The choice of the subject of the research ((Transparency and its effect on quality of message announcement of Insurance company)), which aims to measure the effect of Transparency on the announcement message quality of Insurance services. Came in the time when many countries tend to depend on services in their economics to obtain the per mentioned aim of the research, a hypothetical model was built, that involved the dependent and independent variables and sub variables. Based on the model movement, one main hypothesis is formulated. To test the validity of hypotheses, two random samples were chosen. The first sample which consists of 46 individuals presented general managers, branches managers and workers in National Insurance Company)). The second sample, which consists of 39 individuals, presented the meant audience ((insured and noninsured)).The information’s about the two samples of research were collected by using the Questionnaire and a collection of annual reports, and data were processed by using a group of unparametric and descriptive statistical means to study the relationship and effect between the research variables and dimensions.